Springer Handbook of Ocean Engineering [electronic resource] - Dhanak, Manhar R.; Xiros, Nikolaos I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The handbook is the definitive reference for the interdisciplinary field that is ocean engineering. It integrates the coverage of fundamental and applied material and encompasses a diverse spectrum of systems, concepts and operations in the maritime environment, as well as providing a comprehensive update on contemporary, leading-edge ocean technologies. Coverage includes but is not limited to; an overview of ocean science, ocean signals and instrumentation, coastal structures, developments in ocean energy technologies, and ocean vehicles and automation. The handbook will be of interest to practitioners in a range of offshore industries and naval establishments as well as academic researchers and graduate students in ocean, coastal, offshore, and marine engineering and naval architecture.
Part A Fundamentals (Ed. Manhar Dhanak) -- Part B Autonomous Ocean Vehicles, Subsystems and Control (Ed. Thomas Curtin) -- Part C Coastal Design (Eds Jennifer L. Irish, James M. Kaihatu) -- Part D Offshore Technologies (Eds R. Cengiz Ertekin / Dominique Roddier) -- Part E Energy Resources (Ed. Nikolas I. Xiros) -- Acknowledgements -- About the Authors -- Subject Index.
Keywords: Engineering; Oceanography; Coasts